1999
DOI: 10.1016/s0954-6111(99)90061-6
|View full text |Cite
|
Sign up to set email alerts
|

A confidential enquiry into certified asthma deaths in the North of England, 1994–1996: influence of co-morbidity and diagnostic inaccuracy

Abstract: To understand more fully the nature of events leading to asthmatic death, we conducted a confidential enquiry prospectively throughout 1994-96 among the surviving relatives and respective general practitioners of subjects whose deaths could be attributed to asthma, whether wholly or partly. We also reviewed relevant hospital records and autopsy reports, and we submitted all the gathered information to an enquiry panel for evaluation. The subjects were identified from death certificates issued in five districts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Primary outcome Morning PEF Secondary outcomes Evening PEF Use of rescue medication Day-and night-time asthma symptoms scores % symptom-free days and nights FEV 1 morning PEF for several periods during their 24-week study. The closest data to the end-point that they provided was for weeks [13][14][15][16][17][18][19][20][21][22][23][24]. During this period, the mean ± SD change in the morning PEF from baseline (adjusted by ANCOVA for sex, age and country) was 410 ± 4.49 l/minute for subjects on FP/SAL and 384 ± 4.69 l/minute for subjects on high-dose (1600 µg/day) BUD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary outcome Morning PEF Secondary outcomes Evening PEF Use of rescue medication Day-and night-time asthma symptoms scores % symptom-free days and nights FEV 1 morning PEF for several periods during their 24-week study. The closest data to the end-point that they provided was for weeks [13][14][15][16][17][18][19][20][21][22][23][24]. During this period, the mean ± SD change in the morning PEF from baseline (adjusted by ANCOVA for sex, age and country) was 410 ± 4.49 l/minute for subjects on FP/SAL and 384 ± 4.69 l/minute for subjects on high-dose (1600 µg/day) BUD.…”
Section: Resultsmentioning
confidence: 99%
“…In the period closest to the end of the study (weeks [13][14][15][16][17][18][19][20][21][22][23][24], the median percentage of symptom-free days was 75% for subjects who received FP/SAL and 40% for subjects who received high-dose (1600 µg/day) BUD (these data were estimated by the reviewers from Figure 3a of Jenkins and colleagues 223 ). The respective median percentages of symptom-free days over the whole study (weeks 1-24) for these drugs were 60 and 34% (95% CI 2 to 11).…”
Section: Symptomsmentioning
confidence: 99%
“…However, v10% of deaths certified by doctors in England and Wales include information from a post mortem [6] and this may lead to some inaccuracies in the certified cause of death. Studies of death certificates suggest that a label of asthma may be preferentially applied to females with COPD and that some asthma deaths are recorded as COPD and vice versa [16,17]. Because of this and variations in physician preferences for the various COPD codes, the current authors chose to analyse OLD comprising all COPD and asthma codes.…”
Section: Discussionmentioning
confidence: 99%
“…1 2 Nevertheless, recent confidential enquiries still suggest that many of these premature deaths may be preventable. [3][4][5][6][7][8] Previous case-control studies and audits of asthma deaths have suggested that risk factors fall into four main categories: (1) severity of the disease; (2) medical care factors (both in terms of the nature of the health care system and the management of the mortal event) 3 5 6 8-12 ; (3) health behaviour (adherence to management) 3 5-8 10 12 ; and (4) adverse psychosocial factors. 3-6 8 10 13 If psychosocial and health behaviour factors are important, this may offer opportunities for prevention, particularly as medical management continues to improve.…”
mentioning
confidence: 99%